Idiom Langgar, Surau, Musala dalam Perspektif Fikih - Muhammad Madarik (LPPI Universitas Al-Qolam Malang, 2024)
The basis of this discussion is attempted to be more comprehensive by basing it on two things that are considered quite basic, namely: First, traced from the concepts of mosques in the perspective of classical books (kutub al-turats). This is attempted through content analysis of the scattered yellow book texts in various fiqh studies. Second, examined from the perspective of the socio-religious traditions of Indonesian society. From the perspective of terminological discussion (ishthilahi), the building used as a place for congregational prayer in the texts of the Qur'an, the Sunnah, and books of fiqh only knows the name